Disease Control With Delayed Salvage Radiotherapy for Macroscopic Local Recurrence Following Radical Prostatectomy - Shelan, Mohamed; Odermatt, Seline; Bojaxhiu, Beat; Nguyen, Daniel P.; Thalmann, George N.; Aebersold, Daniel M.; Dal Pra, Alan (Frontiers in Oncology, 2019)
Purpose: To retrospectively assess clinical outcomes and toxicity profile of prostate cancer patients treated with delayed dose-escalated image-guided salvage radiotherapy (SRT) for macroscopic local recurrence after radical prostatectomy (RP). Material and Methods: We report on a cohort of 69 consecutive patients with local recurrence after RP and no evidence of regional or distant metastasis who were referred for salvage radiotherapy between 2007 and 2016. SRT consisted of 64-66 Gy (2 Gy/fraction) to the prostatic bed followed by dose escalation to 72-74 Gy (2Gy/fraction) to the macroscopic disease. All patients received concurrent short-term androgen deprivation therapy (ADT). Biochemical recurrence-free survival (bRFS) and clinical progression-free-survival (cPFS) were depicted using Kaplan-Meier method. Multivariable Cox proportional hazards regression assessed predictors of survival outcomes. Baseline, acute and late urinary and gastrointestinal (GI) toxicity rates were reported using CTCAE v4.03. Results: Median time from RP to SRT was 66 months (IQR: 32-124). Median pre-SRT prostate-specific antigen (PSA) was 2.7 ng/ml (IQR: 0.9-6.5). Median follow-up after SRT was 38 months (IQR: 24-66). The 3- and 5-year bRFS were 58% and 44%, respectively. The 3- and 5-year cPFS were 91% and 76%, respectively. Median time from SRT to clinical disease progression was 102 months (IQR 77.5-165). In multivariable analyses, pre-SRT PSA level was an independent predictor of bRFS, but not of cPFS. At baseline, 3 patients (4%) had grade 3 urinary symptoms. Six patients (9%) developed acute and six patients (9%) developed late grade 3 urinary toxicity. Five patients (7%) had acute grade 2 GI toxicity. No acute grade 3 GI toxicity was reported. Late grade 3 GI toxicity was reported in one patient (1.5%). Conclusions: Delayed dose-escalated SRT combined with short-course ADT for macroscopic LR after RP was associated with 44% bRFS and 76% cPFS at 5 years. Albeit improved patient stratification is warranted, these data suggest that delayed SRT provides inferior tumor control compared to early intervention.